Optimizing antibiotic use in culture-negative healthcare-associated infection with a 'stop' policy: a descriptive analytical study. (5th December 2022) - Sathyan, Sajina; Pournami, Femitha; Prithvi, Ajai Kumar; Nandakumar, Anand; Prabhakar, Jyothi; Jain, Naveen
Abstract: Background and objectives: Many sick neonates receive antibiotics for the clinical diagnosis of probable/possible sepsis. Reports suggest rampant antibiotic use in culture-negative sepsis. We introduced an antibiotic stop policy (ASP), by defining 'completed course duration of antibiotics' in the setting of culture-negative suspected healthcare-associated infection (HAI). Antibiotic overuse days (AOD) before antibiotic stop policy (BASP) and after antibiotic stop policy (AASP) were compared. Methods: This descriptive analytical study was conducted to measure the change in AOD after implementing ASP in culture-negative HAI. We also sought to evaluate situations in which antibiotic overuse is likely (lower gestation, ventilation, central lines) and safety of the ASP, measured as not having to restart antibiotics in the week following completed course. Results: A total of 126 neonates were initiated on a new antibiotic (started or changed) for suspected HAI. Of these, 43 were excluded. Patient days of 5175 and 5208 were analyzed in BASP and AASP, respectively. Implementation of an ASP reduced AOD (from 14.49 to 3.26 AOD per 1000 patient days; p value <0.01). Safety was ensured; the number of babies who had to be restarted on antibiotics within 1 week of stopping therapy was similar in both groups. All-cause mortality and relevant morbidities were comparable between groups. Conclusions: A significant decrease in AOD after the introduction of an ASP was noted, in neonates with culture-negative suspected HAI. This difference was noted even in the most vulnerable extreme preterm babies and those requiring ventilation and central lines.